Biology of AQP4 and Anti-AQP4 Antibody: Therapeutic Implications for NMO - Verkman, A. S.; Phuan, Puay-Wah; Asavapanumas, Nithi; Tradtrantip, Lukmanee (Brain pathology (Zurich, Switzerland), 2013)
The water channel aquaporin‐4 (AQP4) is the target of the immunoglobulin G autoantibody (AQP4‐IgG) in neuromyelitis optica (NMO). AQP4 is expressed in foot processes of astrocytes throughout the central nervous system, as well as in skeletal muscle and epithelial cells in kidney, lung and gastrointestinal organs. Phenotype analysis of AQP4 knockout mice indicates the involvement of AQP4 in water movement into and out of the brain, astrocyte migration, glial scar formation and neuroexcitatory phenomena. AQP4 monomers form tetramers in membranes, which further aggregate to form supramolecular assemblies called orthogonal arrays of particles. AQP4‐IgG is pathogenic in NMO by a mechanism involving complement‐ and cell‐mediated astrocyte cytotoxicity, which produces an inflammatory response with oligodendrocyte injury and demyelination. AQP4 orthogonal arrays are crucial in NMO pathogenesis, as they increase AQP4‐IgG binding to AQP4 and greatly enhance complement‐dependent cytotoxicity. Novel NMO therapeutics are under development that target AQP4‐IgG or AQP4, including aquaporumab monoclonal antibodies and small molecules that block AQP4‐IgG binding to AQP4, and enzymatic inactivation strategies to neutralize AQP4‐IgG pathogenicity.